Intensitas Badan Permusyawaratan Desa Wongsorejo Dalam Mewujudkan Good Governance - Pitaloka, Noviany Roro Ayu; Imaniar, Dimas; Priyanto, Hary (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The BPD's equal position with the Village Government is a consequence of the implementation of regional autonomy. The BPD has the authority to absorb community aspirations, discuss and approve draft Village Regulations, supervise the performance of the Village Head, and create harmonious working relationships with all parties. However, not all BPDs carry out their main duties and functions effectively. This reality can be seen from the performance of BPD Wongsorejo, which in the 2022 budget year only has 1 activity. The impact is that the public does not understand and feel the main duties and functions of the BPD. This research describes, analyzes and interprets the role of BPD Wongsorejo in realizing good governance in Wongsorejo Village, Banyuwangi. Researchers have qualitative principles according to the constructive and participatory model. Primary data comes from interviews and secondary data comes from literature reviews and regulations relevant to the substance of the research. The results and conclusions obtained are that BPD is not just about institutional status but leads to responsibility to participate in creating sustainable, inclusive, effective and efficient village development. The implementation of BPD Wongsorejo's performance in supporting the success of village government must be proven in real terms.